The changes in Alkaline, Neutral and Acid Protease Activities of Artemia Enriched with Commercial Emulsion and Different Additive Combinations - Mehmet Naz; Gürkan Diken; Metin Yazıcı; Yavuz Mazlum; Selin Sayın; Oktay Söyler (Aquatic Sciences and Engineering)
The biochemical compositions and the changes observed in alkaline, neutral and acid protease activities of Artemia enriched with commercial emulsion and different additive combinations were determined. Artemia nauplii (ArtN), GroBiotic-A (GA), Red Algamac (RA), Red Algamac:GroBiotic-A (50:50) (RA:GA (50:50)), Spirulina (SP), Spirulina:Red Algamac (50:50) (SP:RA (50:50)), Spirulina:GroBiotic-A (50:50) (SP:GA (50:50)) and Spirulina:Red Algamac:GroBiotic-A (33:33:33) (SP:RA:GA (33:33:33)) were tested in the study. The lowest and highest protein contents after the enrichment of Artemia were 40.74±1.02% (RA) and 55.03±1.26% (SP:RA:GA (33:33:33)), respectively. The lowest lipid contents of tested groups were found in 5.63±0.47% (GA) and 5.63±0.84% (RA:GA (50:50)). The highest lipid value after the enrichment were observed in 16.98±1.15 % (RA). The lowest and highest ash values observed after the enrichment were 4.51±0.27% (SP:GA (50:50)) and 6.07±0.35% (RA) (p<0.05). The lowest and highest protease activities of the pH=3, pH=4, pH=5, pH=6, pH=7 and pH=8.5 values were 18.18±0.37 U/mg protein (GA), 31.04±0.38 U/mg protein (RA), 9.1±0.32 U/ mg protein (SP), 9.66±0.19 U/mg protein (SP), 16.94±0.61 U/mg protein (SP), 63.09±0.75 U/mg protein (SP) and 33.77±0.59 U/mg protein (RA:GA (50:50)), 57,54±0.34 U/mg protein (RA:GA (50:50)), 23.75±0.28 U/mg protein (GA), 40.82±0.49 U/mg protein (GA), 69.94±0.65 U/mg protein (GA), and 286.14±8.2 U/mg protein (GA) (p<0.05). In conclusion, GA and SP:RA:GA (33:33:33) enrichment combinations are recommended as an alternative to enrichment products. On the other hand, SP and RA should not be used alone due to the disadvantages such as the biochemical composition and proteolytic enzyme activities of Artemia observed in the present study.